KUALITAS LAPORAN KEUANGAN: LATAR BELAKANG PENDIDIKAN DAN PENGALAMAN INTERNASIONAL CFO - Kaban, Melania Berta Uli; Ferby Mutia Edwy (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
Quality financial reports are very necessary for the smooth running of company operations. Companies need competent managers to improve the quality of financial reports. Incompetent managers can result in poor-quality financial reports, causing information asymmetry, damage to the company's reputation, and decreased investor confidence which can hamper the company's operational activities. This research aims to determine the effect of the Chief Financial Officer (CFO) who is a graduate of a reputable university and has international experience in the field of finance on the quality of financial reports. This research was conducted on 563 companies listed on the IDX from 2010 to 2019. Through regression Generalized Least Square (GLS), research finds that CFOs who graduate from reputable universities tend to be able to improve the quality of financial reports, but not CFOs who have international experience in the financial sector. This research shows that the CFO's educational background is very important in supporting the improvement of the quality of financial reports. Therefore, companies must pay attention to the CFO's educational background to support the manager's performance in improving the quality of financial reports.